Sexually Transmitted Infections Prevention Service Utilization and Associated Factors Among University and College Students in Nekemte City: A Mixed-Methods Study - Abiriham Rata; Fedasa Guja; Markos Desalegn; Habtamu Oljira; Dessalegn Wirtu (SAGE Open)
The utilization of sexually transmitted infection prevention services is an important component in preventing different sexual and reproductive health problems. Little is known about the Sexually Transmitted Infections prevention service utilization in the study area. This study aimed to assess Sexually Transmitted Infections prevention service utilization and associated factors among University College Students in Nekemte city. Institution-based cross-sectional study mixed with a qualitative method was employed. The data were collected from May 1 to 31, 2022. Multi-stage sampling technique was used to select 710 study participants. Binary logistic regression was performed and variables with a p -value less than .25 were entered into multivariable logistic regression analysis. For the qualitative study, data saturation was used as a guide to decide on a number of focus group discussions and thematic analysis done. The overall Sexually Transmitted Infections prevention service utilization among university and college students was 19.5%, [95% CI = 16.5, 22.5]. Previous urban residence [AOR 3.73, [95% CI = 2.34, 5.94], having good Knowledge [AOR 4.17, [95% CI = 2.58, 6.76], Ever visited a health facility [AOR 2.88, [95% CI = 1.68, 4.92], Ever been diagnosed with STIs [AOR 3.28, [95% CI = 1.57, 6.85] and, Lack of confidentiality [AOR 0.30, [95% CI = 0.19, 0.49] were significantly associated with sexually transmitted infection prevention service utilization. The level of Sexually Transmitted Infection prevention service utilization was low. Therefore, health facilities should provide services in a private room and health professionals should keep confidentiality to improve Sexually Transmitted Infection prevention service utilization.